Mechanisms of Cell Volume Regulation in Mouse Oocytes: The Role of Zona Pellucida Detachment in the Initiation of Glycine-Dependent Osmoregulation - Ortman, Chyna (Université d'Ottawa / University of Ottawa, 2023)
Mouse oocytes and early preimplantation (PI) embryos possess a novel mechanism for regulating their cell volume which involves the accumulation of the organic osmolyte glycine via the glycine transporter, GLYT1. When the oocyte is still housed within the follicle, oocyte volume is completely determined by its strong adhesion to its rigid extracellular matrix, the zona pellucida (ZP). Shortly following ovulation, the ZP will detach from the oocyte and GLYT1 will become active, allowing the oocyte to independently regulate its own cell volume. These two mechanisms unfold at a very similar time course, with speculation that detachment precedes GLYT1 activation. However, their relative timing has yet to be confirmed. Moreover, much about these mechanisms, such as if they are coupled, remains unknown. Here I explore the relationship between GLYT1 activation and oocyte-ZP detachment, with the data demonstrating that detachment precedes GLYT1 activation. I have found that the inhibition of oocyte-ZP detachment prevents the activation of GLYT1, which implies that GLYT1 activation requires detachment of the ZP from the oocyte. Previous data from our laboratory found that the oocyte-ZP adhesion is released via the action of a metalloproteinase (MP). MP’s are protease enzymes whose catalytic mechanism involves a metal. Therefore, in an attempt to uncover the relationship between detachment and GLYT1 activation, metalloprotease inhibitors were used. Based on these results, I hypothesized that removal of the ZP would accelerate the activation of GLYT1. However, no acceleration was found. Lastly, as TIMPs are an important regulator of MP activity, I tested whether they were able to prevent the MP responsible for ZP detachment. However, detachment still preceded as normal in the presence of TIMPs. Overall, I have built on the previous data from our laboratory to provide further understanding into the two independent cell volume regulation mechanisms of oocyte-ZP detachment and GLYT1 activation.
Keywords: Osmoregulation; Glycine; Zona pellucida; Oocytes